2013
DOI: 10.1021/es304898r
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oxidation Kinetics and Mechanism of Preservative Propylparaben Degradation in Aqueous Suspension of TiO2 and Risk Assessment of Its Degradation Products

Abstract: ABSTRACT:The absolute kinetic rate constants of propylparaben (PPB) in water with different free radicals were investigated, and it was found that both hydroxyl radicals (HO • ) and hydrated electrons could rapidly react with PPB. The advanced oxidation kinetics and mechanisms of PPB were investigated using photocatalytic process as a model technology, and the degradation was found to be a pseudo-first-order model. Oxidative species, particularly HO• , were the most important reactive oxygen species mediating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 164 publications
(85 citation statements)
references
References 55 publications
14
69
0
Order By: Relevance
“…Therefore, R set route was less spontaneous than other exothermic routes and could be difficult to occur in the initial step of MPB degradation, indicating a very low probability for the electron-transfer reactivity of parabens with • OH. The finding also explains the previous experimental results, i.e., the transient spectrum of the single-electron transfer product, the radical cation of propylparaben (PPB +* ), was not observed during the degradation of propylparaben using AOPs [37]. Based on the above discussion, the single-electron transfer route (R set ) and two OH-addition routes (R add 3 and R add 7) can be ruled out during MPB degradation using AOPs because of the endothermic processes.…”
Section: Initial Reaction Of Mpb With • Ohsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, R set route was less spontaneous than other exothermic routes and could be difficult to occur in the initial step of MPB degradation, indicating a very low probability for the electron-transfer reactivity of parabens with • OH. The finding also explains the previous experimental results, i.e., the transient spectrum of the single-electron transfer product, the radical cation of propylparaben (PPB +* ), was not observed during the degradation of propylparaben using AOPs [37]. Based on the above discussion, the single-electron transfer route (R set ) and two OH-addition routes (R add 3 and R add 7) can be ruled out during MPB degradation using AOPs because of the endothermic processes.…”
Section: Initial Reaction Of Mpb With • Ohsupporting
confidence: 90%
“…However, opposite result was observed in the subsequent reaction with • OH. This can well explain experimental results as to why mono-hydroxylated paraben was first observed and then converted into highly hydroxylated products in the aerated aquatic environments [37].…”
Section: Subsequent Reactions Of Oh-addition and H-abstraction Intermsupporting
confidence: 74%
“…Excellent removal efficiencies (98.8-100%) were observed in the process of ozonation, which is in agreement with previous result that an amount of ozone could result in the removal of 99% of parabens in a short time [46]. The reaction kinetics and degradation mechanism of parabens during ozonation were investigated in several studies, and it has been shown that both hydroxyl radicals and hydrated electrons could rapidly react with parabens during this process [47][48][49]. Because of their high removal efficiencies in the conventional treatment, only a small fraction of parabens was further reduced by the ozonation.…”
Section: Advanced Treatment Processessupporting
confidence: 88%
“…All the ratios are much lower than 1, indicting that parabens and their chlorinated derivatives are not likely to produce biological effects at environmentally relevant levels in aquatic ecosystems. Taking into consideration the fact that several degradation products with higher toxicity than their parent parabens would form in the advanced oxidation [47,48], the risks of parabens, especially the degradation products, on organisms required further investigations.…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%
“…Photocatalytic (PC) degradation of a wide spectrum of organic compounds via TiO 2 photocatalysis has been well studied and documented [1][2][3][4][5]. Successful demonstration of the ability of illuminated TiO 2 for disinfection and decomposition of microorganisms has led to a new application field of TiO 2 photocatalysis [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%